Application of Plasmonic Nanoantennas in Enhancing the Efficiency of Organic Solar Cells. (10th March 2020) - da Silva, Marcelino L. C.; Dmitriev, Victor; da Costa, Karlo Q.
Abstract : It is known that the periodic use of silver nanoantennas in organic solar cells increases the efficiency of light absorption. In this study, we performed a geometric parametric analysis of nanoantennas using the finite element method. Based on the study of the convex truncated cone nanoantenna, we have found that a nanoantenna arrangement formed by the convex truncated cone nanoantenna along with a pyramidal nanoantenna provides a better solution for different angles of light incidence compared to a single nanoantenna. We obtained a mean increase in the absorption efficiency of this organic solar cell, both for the TM and TE polarizations, compared to the use of the conventional nanoantenna in the wavelength range of 300–800 nm.